SOSIALISASI PERHITUNGAN HARGA POKOK PENJUALAN KEPADA UMKM DI STASIUN GONDANGDIA, JAKARTA PUSAT - Tanjung Prasetyo; Kayla Maysel Maharani; Khadijah; Khansa Ananda Triesdianto (Jurnal Humaniora & Sosial Sains, 2024)
Even though MSMEs are an important part of the Indonesian economy, many of them still face problems in financial management, especially in calculating the correct cost of goods sold (COGS). The aim of this study is to determine the extent to which training in calculating the cost of goods sold (COGS) can increase the knowledge and ability of MSMEs to set competitive selling prices. Socialization participants are five small and medium companies (MSMEs) operating in the food and beverage industry in the central area of Jakarta. Lectures, discussions and practices are part of the participatory approach used. Courses on the basic principles of cost accounting, cost classification, and how to calculate the costs of raw materials, direct labor, and factory overhead were given to participants. After the training, MSME owners found that participants' understanding of the COGS concept increased by 85% and their ability to calculate COGS increased 75%. They also recognize the benefits of training for their business in determining competitive selling prices and increasing profits. In conclusion, socializing the calculation of cost of goods sold (HPP) has proven effective in helping MSMEs manage their finances and set the right selling price. It is recommended that similar training be held regularly and reach more MSMEs so that they can develop and survive for a long time.